Performance and Stability of Pearl Millet Varieties for Grain Yield and Micronutrients in Arid and Semi-Arid Regions of India - Sanjana Reddy, P.; Satyavathi, C. Tara; Khandelwal, Vikas; Patil, H. T.; Gupta, P. C.; Sharma, L. D.; Mungra, K. D.; Singh, Sumer P.; Narasimhulu, R.; Bhadarge, H. H.; Iyanar, K.; Tripathi, M. K.; et al. (Frontiers in Plant Science, 2021)
Pearl millet [Pennisetum glaucum (L.) R. Br.] is grown under both arid and semi-arid conditions in India where other cereals are hard to grow. Pearl millet cultivars - hybrids and OPVs (Open Pollinated Varieties) are tested and released by the All India Coordinated Research Project on Pearl Millet (AICRP-PM) across the three zones (A1, A, and B) that are classified based on rainfall pattern. The OPVs are important due to wider adaptation, lower input cost and timely seed availability to subsidiary farmers cultivating this crop. This study was conducted to scrutinize the presently used test locations for evaluation of pearl millet OPVs across India, identify the best OPVs across locations and determine variation of grain Fe and Zn contents across locations in these regions. Six varieties were evaluated across 20 locations in A1 and A (pooled as A) and B zones along with 3 common checks and additional 3 zonal adapted checks in respective zones during 2019 rainy season. Data recorded on yield and quality traits were analyzed using genotype main effects and genotype × environment interaction biplot method. Genotype × environment (G×E) interaction was found to be highly significant for all the grain yield and agronomic traits and for both micronutrients (iron and zinc). However Genotypic effect (G) was 4 (productive tillers) to 49 (grain Fe content) times that of G×E interaction effect for various traits across zones that shows the flexibility of the OPVs. Ananthapuramu is the ideal test-site for selecting pearl millet cultivars effectively for adaptation across India while Ananthapuramu, Perumallapalle and Gurugram can also be used as initial testing locations. The OPVs MP 599 and MP 600 are identified as the ideal genotypes as they showed higher grain and fodder yields and stability compared with other cultivars. Iron and zinc concentration showed highly significant positive correlation (across environment = 0.83; p < 0.01) indicating possibility of simultaneous effective selection for both the traits. Three common checks were found to be significantly low yielders than the test entries or zonal checks in individual zones and across India indicated the potential of genetic improvement through OPVs.